Letters of guarantee in construction contracting (FIDIC (Journal of the College of Basic Education, 2022)
Letters of guarantee occupied an important position in all economic fields in general and in the field ofConstruction Contracting (FIDIC) contracts in particular as an alternative to placing a cash amount byContracting is under the employer's hand to ensure the seriousness of this contractor in entering the tender, or the good performance ofWork during implementation, or ensure project maintenance and repair of defects that appear during the maintenance period.And after issuing a certificate for final delivery, and then finally ensuring that the employer will recover the advance payment that